2018
DOI: 10.1080/17461391.2017.1421711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute ingestion of β‐hydroxybutyrate salts on the response to graded exercise in trained cyclists

Abstract: Acute ingestion of ketone salts induces nutritional ketosis by elevating β-hydroxybutyrate (βHB), but few studies have examined the metabolic effects of ingestion prior to exercise. Nineteen trained cyclists (12 male, 7 female) undertook graded exercise (8 min each at ∼30%, 40%, 50%, 60%, 70%, and 80% VO) on a cycle ergometer on two occasions separated by either 7 or 14 days. Trials included ingestion of boluses of either (i) plain water (3.8 mL kg body mass) (CON) or (ii) βHB salts (0.38 g kg body mass) in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
8
47
2
Order By: Relevance
“…We found that neither administration nor dose of βHB+MCT in uenced heart rate, RR, RER, VO 2 , VCO 2 , VE, or estimated metabolic oxidation rates. HR has elevated with ketone salts administration [15,16] or reductions in HR with ester administration [18,20], with the vast majority consistent with our ndings across exogenous ketone supplements [19,[21][22][23]25]. While most exogenous ketone evaluations have not observed changes in RER in agreement with our observations, some analyses have observed differences [8,13,14].…”
Section: Cognitive Performancesupporting
confidence: 87%
See 4 more Smart Citations
“…We found that neither administration nor dose of βHB+MCT in uenced heart rate, RR, RER, VO 2 , VCO 2 , VE, or estimated metabolic oxidation rates. HR has elevated with ketone salts administration [15,16] or reductions in HR with ester administration [18,20], with the vast majority consistent with our ndings across exogenous ketone supplements [19,[21][22][23]25]. While most exogenous ketone evaluations have not observed changes in RER in agreement with our observations, some analyses have observed differences [8,13,14].…”
Section: Cognitive Performancesupporting
confidence: 87%
“…Ketone salts and/or βHB+MCT have not shown an ability to attenuate exercise lactate productions, consistent with the present ndings [13][14][15][16]25]. However, attenuated lactate production is more consistently observed with ester administration [8,18,20], although it does not always reach signi cance [21,22].…”
Section: Cognitive Performancesupporting
confidence: 84%
See 3 more Smart Citations